PucC and LhaA direct efficient assembly of the light‐harvesting complexes in Rhodobacter sphaeroides. Issue 2 (5th November 2015) - Mothersole, David J.; Jackson, Philip J.; Vasilev, Cvetelin; Tucker, Jaimey D.; Brindley, Amanda A.; Dickman, Mark J.; Hunter, C. Neil
Summary: The mature architecture of the photosynthetic membrane of the purple phototroph R hodobacter sphaeroides has been characterised to a level where an atomic‐level membrane model is available, but the roles of the putative assembly proteins LhaA and PucC in establishing this architecture are unknown. Here we investigate the assembly of light‐harvesting LH2 and reaction centre‐light‐harvesting1‐PufX (RC‐LH1‐PufX) photosystem complexes using spectroscopy, pull‐downs, native gel electrophoresis, quantitative mass spectrometry and fluorescence lifetime microscopy to characterise a series of lha A and puc C mutants. LhaA and PucC are important for specific assembly of LH1 or LH2 complexes, respectively, but they are not essential; the few LH1 subunits found in Δ lha A mutants assemble to form normal RC‐LH1‐PufX core complexes showing that, once initiated, LH1 assembly round the RC is cooperative and proceeds to completion. LhaA and PucC form oligomers at sites of initiation of membrane invagination; LhaA associates with RCs, bacteriochlorophyll synthase (BchG), the protein translocase subunit YajC and the YidC membrane protein insertase. These associations within membrane nanodomains likely maximise interactions between pigments newly arriving from BchG and nascent proteins within the SecYEG‐SecDF‐YajC‐YidC assembly machinery, thereby co‐ordinating pigment delivery, the co‐translational insertion of LH polypeptides and their folding and assembly to form photosynthetic complexes. Abstract : LhaA and PucC form oligomers at the sites where invagination of the cytoplasmic membranes is initiated, and they play important roles in photosystem assembly in the purple phototrophic bacterium Rhodobacter sphaeroides. Establishing the architecture of the photosynthetic membrane involves interplay between LhaA, reaction centre complexes, bacteriochlorophyll synthase, the protein translocase subunit YajC, and the YidC membrane protein insertase. These associations likely coordinate the delivery of pigments and the membrane insertion, folding and assembly of photosystem polypeptides.